The impact of obesity on laparoscopic liver surgery: a critical reappraisal - Machairas, Nikolaos; Sotiropoulos, Georgios C. (Laparoscopic Surgery, 2018)
Laparoscopic liver surgery has been demonstrated to be a safe and efficient approach in the treatment of several hepatic lesions (1-3). Laparoscopic liver resections (LLR) are increasingly performed worldwide (4); nevertheless, their utility in patients with increased body mass index (BMI) remains ill-determined.